Stare in the darkness : the limits of hip-hop and Black politics - Spence, Lester K. (University of Minnesota Press, 2011)
Rap's critique of police brutality in the 1980s. The Hip Hop Political Convention. The rise (and fall) of Kwame Kilpatrick, the "hip-hop mayor" of Detroit. Barack Obama echoing the body language of Jay-Z on the campaign trail. A growing number of black activists and artists claim that rap and hip-hop are the basis of an influential new urban social movement. Simultaneously, black citizens evince concern with the effect that rap and hip-hop culture exerts on African American communities. According to a recent Pew survey conducted on the opinions of Black Americans, 71 percent of black